2018
DOI: 10.1159/000491732
|View full text |Cite
|
Sign up to set email alerts
|

Interferon Regulatory Factor 1 Activates Autophagy to Aggravate Hepatic Ischemia-Reperfusion Injury by Increasing High Mobility Group Box 1 Release

Abstract: Background/Aims: Interferon regulatory factor 1(IRF-1) and high mobility group box 1(HMGB1) have been independently identified as being key players in hepatic ischemia-reperfusion injury (IRI). We attempted to determine whether IRF-1 activates autophagy to aggravate hepatic IRI by increasing HMGB1 release. Methods: The hepatic IRI model was generated in C57BL/6 mice, euthanized at 2, 6, 12 or 24 h after reperfusion. To examine the effects of HMGB1 release inhibition, Glycyrrhiza acid (GA) was administered to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 30 publications
0
19
0
Order By: Relevance
“…Of particular relevance to the present investigation is the report that levels of IRF‐1 increase within the liver after IR exposure 12 . Moreover, IRF‐1 knockout, which reduces the expression and release of high mobility group protein (HMGB1), relieves liver IRI 13 …”
Section: Introductionmentioning
confidence: 72%
“…Of particular relevance to the present investigation is the report that levels of IRF‐1 increase within the liver after IR exposure 12 . Moreover, IRF‐1 knockout, which reduces the expression and release of high mobility group protein (HMGB1), relieves liver IRI 13 …”
Section: Introductionmentioning
confidence: 72%
“…These results were similar with the previous reports showing IRF-1 played an important role in ischemic neuronal death in mice or dead ischemic patients [ 15 ]. IRF-1 was also reported to aggravate hepatic ischemic/reperfusion injury [ 42 ]. Our results also showed that activating LXRs inhibited the expression of IRF-1 on transcription level, which was in agreement with previous reports showing that LXR ligands inhibit neither STAT1 phosphorylation nor STAT1 translocation to the nucleus but rather inhibit STAT1 binding to the promoters and the expression of IRF-1 [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…IRF-1 plays a harmful role in liver IR [ 12 , 13 ], as well as reperfusion injury in other organs [ 12 , 14 , 15 ]. More recently, IRF-1 KO mice studies have shown that inhibiting autophagy was protective in hepatic IR [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%